Untimely snowfalls - An emerging concern for temperate fruit growers in Kashmir valley - Kumawat, K L; Sharma, Anil; Raja, W H; Sharma, O C; Mir, J I (Indian Horticulture, 2022)
The horticulture sector is perceived as the backbone of the Jammu and Kashmir economy as it significantly contributes to Gross State Domestic Production. Around 7 lakh families, comprising 33 lakh people, are directly or indirectly associated with the horticulture sector. During the last few years, the Kashmir fruit growers have suffered a major setback mostly due to climatic variability in particular to the unseasonal heavy snowfall. Based on the time of occurrence, untimely snowfall affect flower parts, pollination process, fruit set, harvesting of late-season varieties, on-farm activities like sorting, grading, packaging, storage, and marketing of produce. In addition, it results in mechanical damage to trees. Furthermore, it can have a significant effect on return bloom by reducing fruit-producing areas on trees. We have no control over the occurrence of pre-and post-winter snowfall but still with the help of some management practices, we can minimize the losses due to untimely snowfall.